How fund managers in Malaysia make decisions. (2nd February 2015) - Glanville bin Mohamad, Samsukri Glanville bin Mohamad; Perry, Chad
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate how fund managers in a non-Western country like Malaysia follow investment processes developed in the West and taught in the finance departments of universities. Design/methodology/approach – This convergent interview research investigates how fund managers in Malaysia actually make their decisions, and develops a framework about their investment process. Findings – Understanding the economy was important for the managers but was an ongoing learning process. Their analyses sometimes started bottom-up or top-down, but all followed a four-layer process. The managers did not believe the investment process could be quantified. Research limitations/implications – Convergent interviewing is meant to be a first step in a complete research program. So, future researchers could consider extending the research to different periods, different research settings in other countries like Singapore, India or Indonesia, different types of investors and different methodologies like surveys. Practical implications – Practitioners should build on their experience, and understand principles of behavioral finance. Students in business schools should be taught in an experiential way, and school staff should use qualitative methods like convergent interviewing in their research projects. Originality/value – Contributions centre on the article's behavioural finance findings that experience and non-quantitative methods are the core of Malaysian investment managers' decision-making, and on its detailed description of the unusual research methodology in finance of convergent interviewing.